Infectious and respiratory vulnerability among elderly women in urban slums in India: the role of informal work and social disadvantage - Deepti Verma; Alka Verma; Preeti Dwivedi; Asif Dabeer Jafri (International Journal Of Community Medicine And Public Health, 2026)
Elderly women working in the informal sector of urban slums in India are highly vulnerable due to the combined effects of ageing, poverty, hazardous occupations, and limited access to healthcare. This review examined published evidence on infectious disease risks in this population, focusing on respiratory health and the influence of social determinants. The evidence showed that biomass fuel exposure, ambient air pollution, overcrowding, poor ventilation, inadequate sanitation, and unsafe waste handling substantially increased respiratory and infectious disease risks. Women engaged in ragpicking and similar occupations faced additional hazards from direct contact with unsegregated municipal and biomedical waste, lack of personal protective equipment, prolonged work hours, anemia, addiction, and social insecurity. Studies also reported a high burden of chronic respiratory disease, recurrent respiratory symptoms, tuberculosis associated with biomass smoke, multi-morbidity, and delayed healthcare seeking due to financial constraints, poor health literacy, limited healthcare access, dissatisfaction with public services, and misattribution of symptoms to ageing. Overall, infectious disease vulnerability is driven by interacting biological, environmental, occupational, and social factors. Targeted policies should prioritize clean household energy, safer waste management, improved slum conditions, accessible geriatric and primary healthcare, and community-based screening and support for socially disadvantaged older women.